2020
DOI: 10.1021/acsmedchemlett.0c00425
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Antimicrobial Peptide Potency through Multivalent Presentation on Coiled-Coil Nanofibrils

Abstract: Antibiotic-resistant microbes have become a global health threat. New delivery systems that enhance the efficacy of antibiotics and/or overcome the resistances can help combat them. In this context, we present FF03, a fibril-forming α-helical coiled-coil peptide that functions as an efficient scaffold for the multivalent presentation of the weakly cationic antimicrobial peptide (AMP) IN4. The resulting IN4-decorated FF03 coiled-coil fibrils (FF03 + IN4) are nonhemolytic and noncytotoxic and show enhanced antim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 70 publications
0
4
0
Order By: Relevance
“…The C 10 -ATRA-1 analogue were also found to adopt a coiled-coil structure in the presence of the artificial lipid membranes. It is believed that the peptides folded in this way can be characterized by lower cytotoxicity [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…The C 10 -ATRA-1 analogue were also found to adopt a coiled-coil structure in the presence of the artificial lipid membranes. It is believed that the peptides folded in this way can be characterized by lower cytotoxicity [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…60 Recently Thota and colleagues demonstrated that the efficacy of a weak cationic antimicrobial peptide (IN4) could be improved by attaching it to a fibril-forming α-helical coiled-coil peptide (FF03). 86 Hydrogel formation was not observed but the fibrous scaffold enhanced the presentation of cationic peptide to bacterial membranes with improved efficacy relative to the unconjugated AMP analogues and reduced toxicity to mammalian cells. The cationic charge density was more readily accessible to interact with anionic bacterial cell membranes via stronger electrostatic interactions.…”
Section: Combining Antimicrobial Peptides With Self-assembling Peptide Sequencesmentioning
confidence: 99%
“…In recent years, peptide-based hydrogels , have been developed as biomaterials that act as antimicrobial agents for the treatment of infectious diseases . Several kinds of hydrogels have been reported so far, , but there are few peptide-based low molecular weight hydrogels that inherently show antimicrobial activity. Polycation moieties have antimicrobial properties, but often show a certain level of toxicity to mammalian cells .…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, this property has been explored to make injectable hydrogels that can be used in localized therapy in a particular tissue. 36 In recent years, peptide-based hydrogels 37,38 have been developed as biomaterials that act as antimicrobial agents 39 for the treatment of infectious diseases. 40 Several kinds of hydrogels have been reported so far, 41,42 but there are few peptide-based low molecular weight hydrogels that inherently show antimicrobial activity.…”
Section: ■ Introductionmentioning
confidence: 99%